Reproductive performance in a Cuban buffalo enterprise - García Quiñones, D.; Fraga, L. M.; García, Yoleisy; Zánchez, A.; Simón, Marlén (Cuban Journal of Agricultural Science, 2018)
The performance of some reproductive indicators was evaluated: calving-calving interval (CCI), service period (SP), incorporation weight (INCW), incorporation age (INCA) and age at first calving (AFC) of 8 buffaloes herds that had calving between 2004 and 2013, in a livestock enterprise at east of Mayabeque province in Cuba. Some dispersion statisticians of the analyzed traits with SAS INSIGHT were studied and the GLIMMIX SAS procedure was used for the statistical analysis. The model used contained the fixed effects of herd, calving year, and calving time and as a covariate to the calving order (1-5) for the first two indicators. For the INCW, INCA and FCA only the herd effect was considered in the model. The herd effect was significant for CCI, INCW and FCA, the year and time of calving for CCI and SP, while the fit for covariance according to the calving order reached the significance for the CCI and SP. The CCI of the years 2007 and 2013 should serve as indications so that future increases of this indicator that affect reproductive efficiency will not occur. The best values of the analyzed indicators were found in herds 212 and 213, which represent positive reference values for the enterprise.Key words: buffalo, performance, reproductive